Peningkatan Keterampilan Menulis Cerita Pendek Menggunakan Media Pop up untuk Siswa Kelas IV SDN Minasa Upa Kecamatan Rappocini Kota Makassar - Nurul Fitri; Ratnawati Ratnawati; Sri Rahayu (Jurnal Pendidikan Indonesia (JOUPI), 2023)
The main problem in this research is how is the process of writing short story skills using pop up media for fourth grade students at SD Minasa Upa, Rappocini District, Makassar City. Rappocini Makassar City. This type of research is classroom action research (CAR), which consists of two cycles where each cycle is held in three meetings. Research procedures include planning, implementation, observation and reflection. The subjects of this study were 32 students of class IV at SDN Minasa Upa, Rappocini District, Makassar City. The results showed that in cycle I there were 16 students who got low scores (50%), 4 students who got fair scores (12.5%) and 16 students who got low scores (50%). Whereas in cycle II 21 there were 26 students who got high scores (81.25%), 2 students who got fair scores (6.25%) and 4 students who got low scores (12.5). Based on the results of observation and evaluation, then it was concluded that the research was stopped in cycle II, the research target of 80% had been fulfilled. As previously stated that by implementing pop up media in class IV SDN Minasa Upa, Rapoccini District, Makassar City, it has increased and after seeing the results of the research that has been analyzed, it can be seen that the results of learning writing skills for class IV students at SDN Minasa Upa, Rapoccini District, Makassar City after applying pop-up media in learning writing skills it has increased. We can see this in the average value of students after the use of pop up media cycle I and cycle II increased from 50% to 81.25%. If it is put into a five-scale category, the increase in learning outcomes in writing skills increases from low to high.